Bioethical Aspects of Improving the Production of Rabies Immunoglobulin in Russia - S. V. Generalov; E. G. Abramova; Yu. K. Gavrilova (Биопрепараты: Профилактика, диагностика, лечение)
The main objective of the present research was to review the studies that look into ways of improving production of anti-rabies immunoglobulin in terms of bioethical principles: ensuring patients’ right to receive quality pharmaceutical care, and compliance with the 3R principles. At the same time, compliance with bioethical principles should contribute to the improvement of production technology and the product quality, which is especially important for antirabies immunoglobulin due to the existing high demand for it. The paper analyses the current trends in avoidance of animal use in the production of rabies immunoglobulin. It summarises the main methods of production of serum products for post-exposure prophylaxis of rabies. The example of heterologous rabies immunoglobulin is used to substantiate the need to improve quality control of drugs by following the 3R principles. The paper highlights the potential use of cell cultures for determination of rabies immunoglobulin specific activity. The authors formulated the objectives that include development and use of pyrogen detection methods which do not involve animal use and are consistent with the current pharmacopoeial standards. They assessed the possibility and feasibility of removing Abnormal Toxicity Test for heterologous rabies immunoglobulin in accordance with the current international trends. The formulated objectives imply optimisation of production of heterologous rabies immunoglobulin in Russia in order to improve the quality of antirabies measures. The objectives include higher production volumes to ensure the availability of the product to patients, reduction of the product reactogenicity by using cell-culture technologies for obtaining rabies antigen, as well as development and implementation of in vitro test methods for product quality control in terms of Specific activity, Pyrogenicity, and Abnormal toxicity